Optimalisasi Layanan Teknik Metafora dalam Bimbingan dan Konseling melalui Pendekatan Kelompok - Habsy, Bakhrudin All; Salsabila, Salsabila; Chueyra, Sankara Pramahadi; Zuhriyah, Sofia Aminatuz; Sholihah, Zizamatus (Al-DYAS, 2024)
Group counseling with a metaphorical approach has been a topic of interest in psychology and counseling literature. This approach utilizes metaphors or analogies to help understand and address problems in a more creative and open way. This study aims to explore the effectiveness of group counseling guidance with a metaphorical approach in improving participants' psychological well-being. The research method used used the literature study method, with regard to data collection methods Library, reading and recording and processing research materials. The results showed that the metaphorical approach in group counseling guidance can provide space for a deeper understanding of individual problems, facilitate creativity in finding solutions, and enhance connections between group participants.